24.0k views
1 vote
Just need this &' three more .

Just need this &' three more .-example-1

2 Answers

7 votes

Answer:

3(x-4)=6x-2(x+3)

3x-12=6x-2x-6

3x-12=4x-6

3x-4x=-6+12

-x=6

:.x=-6

User Abi Chhetri
by
5.4k points
6 votes


\underline{\textbf{\textsf{ \purple{Solution}:- }}}


\sf{\\}
\sf3(x - 4) = 6x - 2(x + 3)
\longrightarrow \sf3x - 12 = 6x - 2x - 6
\longrightarrow\sf3x - 12 = 4x - 6
\longrightarrow\sf3x - 4x = 12 - 6


\longrightarrow\sf -x = 6


\leadsto \underline{\boxed{\mathfrak{ \pink{x = -6} }}}

User Virendra Kumar
by
5.0k points